Effect of CO2/N2/CH4 dilution on NO formation in laminar coflow syngas diffusion flames. Issue 7 (3rd April 2018) - Xi, Jianfei; Yuan, Ye; Gu, Zhongzhu; Yang, Weiben; Zhang, Xianpeng; Wang, Shengfu
ABSTRACT: The effect of CO2 /N2/ CH4 dilution on NO formation in laminar coflow H2 /CO syngas diffusion flames was experimentally and numerically investigated. The results reveal that the NO emission index increases with H2 /CO mole ratio. In all cases, CO2 /N2 /CH4 dilution can reduce the peak temperature of syngas flame and have the ability to reduce peak flame temperature is decreased in the following order: CO2 >N2 >CH4 . CO2 /N2 dilution reduces the NO formation in syngas flame while CH4 dilution promotes the NO formation. Besides, the dilution of CO2 /N2 /CH4 can reduce the peak mole fraction of OH and its variations with H2 /CO mole ratio and dilution ratio show the same trend as the peak flame temperature variations. The height of the flame with CO2 and N2 dilution increases with dilution ratio. The flame with CH4 dilution becomes higher and wider with the increase of dilution ratio.